Factors Affecting Information Technology Acceptance By Health Information Management (HIM) Staff Of Tehran University Of Medical Sciences' Hospitals Based On The Technology Acceptance Model (TAM) In 2011 - Mohammadhiwa Abdekhoda; Maryam Ahmadi; Agha Fateme Hossini; Esmail Prikhani; Akram Farhadi (Tehran University of Medical Sciences, 2013)
Background and Aim: Despite all inherent advantages of information technology in health sector, its implementation still faces many problems. One of the most important barriers is people's resistance. This study was carried out to survey the factors affecting the acceptance of information technology by Health Information Management (HIM) staff of Tehran University of Medical Sciences (TUMS) hospitals based on Technology Acceptance Model (TAM) in 2011. Materials and Methods: It is a descriptive-analytical survey. The population of the study consisted of the HIM staff (363 members) of TUMS hospitals. As the sample, 123 employees were selected. The data gathering tool was a questionnaire the validity and reliability of which were confirmed. The data were collected and analyzed by SPSS software, descriptive statistical methods and Spearman Test. Results: The results showed that there was a positive direct relationship between perceived ease of use (PEOU) on the one hand and the staff's attitude and their application of IT on the other hand (R=0.14, P= 0.05 R=0.36, P=0.05). Also, perceived usefulness (PU) had a significant direct effect on the staff's attitude and their application of IT (R=0.22, P= 0.05 R=0.37, P=0.05). Conclusion : Perceived ease of use (PEOU) and perceived usefulness (PU) are the factors affecting the acceptance of information technology by the HIM staff of TUMS hospitals. Therefore, it is suggested that the above two principles be considered when designing and implementing the IT systems.